Mechanical properties of treadmill surfaces and their effects on endurance running - Colino, E.; Garcia-Unanue, J.; Gallardo, L.; Foster, C.; Lucia, A.; Felipe, J. L. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To characterize, for the first time, the mechanical properties of treadmill surfaces along with a practical interpretation of their influence on physiological and perceived demands during endurance running compared with other widely used surfaces such as asphalt and tartan tracks. Methods: Ten experienced male endurance runners performed a 40-minute running bout at a preferred constant speed on 3 different surfaces (after a randomized, counterbalanced order with a 7-d interval between trials): asphalt, tartan, or treadmill. Shock absorption, vertical deformation, and energy restitution were measured for the 3 surfaces. Intensity (based on heart rate data) and rating of perceived exertion were monitored. Results: The values of shock absorption averaged 0.0% (asphalt), 37.4% (tartan), and 71.3% (treadmill), while those of vertical deformation and energy restitution averaged 0.3, 2.2, and 6.5 mm and 90.8%, 62.6%, and 37.0%, respectively. Running intensity (as determined by heart rate data) was higher overall on the treadmill than tartan but not asphalt running. Except for the first 10 minutes, all mean rating of perceived exertion values were significantly higher in asphalt and treadmill than in tartan. No significant differences were identified between treadmill and asphalt. Conclusions: The considerably higher shock absorption of the treadmill than the tartan surface leads to a reduction in the amount of energy returned to the athlete, which in turn increases physiological stress and rating of perceived exertion during endurance running.